Proverbs and Sayings as Roots of Folk Oral Creativity - kizi, Abdullayeva Shakhnoza Bakhodir (International Journal of Formal Education, 2025)
Proverbs and sayings, as a genre of folk oral creativity, have not lost their relevance in both spoken language and artistic literature to this day. They remain an integral part of every nation’s spiritual values. The origin of proverbs and sayings has preserved its ideological, aesthetic, and cognitive significance since ancient times.